Dyskryminacja mniejszości w prawie i w polityce - Kundera, Weronika (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The problems of minorities are increasingly prevalent in Europe. Fortunately, international law guarantees them justice under the law, equal to that of indigenous populations. In the face of mass migration, intolerance towards persons of different origins, cultures, religions, and customs is growing. This takes the form of indirect and direct discrimination, and it often aims at deporting “foreigners” from a country. Such discrimination manifests itself in public institutions (offices, schools) and in everyday matters (shopping, leasing of flats). Foreigners also become victims of hate (hate crimes), while stereotypes reinforced by society serve intolerance (hatespeech). An extreme type of discrimination is the extermination of foreign communities, fortunately rare in Europe. Complaints about discrimination are considered by the ECJ and the ECJH, which adjudicate in specific matters; indirectly, they shape state policy on minorities.
Keywords: dyskryminacja; asymilacja; segregacja w edukacji; ludobójstwo; orzecznictwo ETS; orzecznictwo ETPCz